Fordyce Spot of Vulva Confused with Condyloma Accuminatum - Salman, Mehmet Coşkun; Himmetoğlu, Çiğdem; Başaran, Derman; Usubütün, Alp; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2008)
Fordyce spots are ectopic sebaceous glands which are most commonly seen on lips and oral mucosa. Patients are asymptomatic and do not require treatment unless cosmetic concerns arise. Fordyce spots can also be seen on vulva. However, in such patients, more common vulvar disorders including condyloma accuminatum may be considered clinically instead of Fordyce spots. Therefore, any vulvar lesion without typical appearance should be sampled and examined histopathologically before initiating treatment. A woman with vulvar Fordyce spots who was misdiagnosed to have condyloma accuminata is presented. The patient admitted to a gynecologist with a complaint of chronic vulvar pruritus. After vulvar inspection, topical imiquimod cream was given with a presumed diagnosis of condyloma accuminatum. The patient then admitted to our hospital without commencing therapy. She was subjected to biopsy after examination due to atypical lesions. Papules located on both labia minora were reported to be Fordyce spots and random biopsy was consistent with chronic inflammation. Therefore, she was given topical corticosteroid instead of imiquimod.